2016
DOI: 10.1080/17436753.2015.1120403
|View full text |Cite
|
Sign up to set email alerts
|

Effect of short carbon fibre concentration on microstructure and mechanical properties of TiCN-based cermets

Abstract: Short carbon fibre (C f ) reinforced TiCN-based cermets (C f /TiCN composites) were produced by powder metallurgy method with pressureless sintering technology. The phase evolution, microstructure and fracture morphology of C f /TiCN composites were investigated. The results showed that TiC, TiN, WC, Cr 3 C 2 and Mo phases disappeared gradually and diffused into core and rim phases by dissolution-reprecipitation process, finally formed new hard TiCN core phases and complex compound (Cr, W, Mo, Ti)(CN) rim phas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…1−4 To fabricate cermets, brittle and hard ceramics, such as carbides (e.g., WC, TiC) and nitrides (e.g., TiN), are usually mixed with malleable and soft metals, such as Fe, Co, Ni, and Mo via powder consolidation techniques. 1 As a result of the mixed ceramic−metallic bonding, cermets usually exhibit superb hardness (15−35 GPa), 2,3 remarkable wear/oxidation resistance, 5,6 and excellent chemical/thermal stability. 2,7,8 Despite this unique combination of physical properties, the Achilles' heel of cermets is their lack of ductility and poor room-temperature toughness (e.g., 5−25 MPam 1/2 ).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…1−4 To fabricate cermets, brittle and hard ceramics, such as carbides (e.g., WC, TiC) and nitrides (e.g., TiN), are usually mixed with malleable and soft metals, such as Fe, Co, Ni, and Mo via powder consolidation techniques. 1 As a result of the mixed ceramic−metallic bonding, cermets usually exhibit superb hardness (15−35 GPa), 2,3 remarkable wear/oxidation resistance, 5,6 and excellent chemical/thermal stability. 2,7,8 Despite this unique combination of physical properties, the Achilles' heel of cermets is their lack of ductility and poor room-temperature toughness (e.g., 5−25 MPam 1/2 ).…”
mentioning
confidence: 99%
“…Cermet is a hybrid/composite material made up of ceramics and metals. To fabricate cermets, brittle and hard ceramics, such as carbides (e.g., WC, TiC) and nitrides (e.g., TiN), are usually mixed with malleable and soft metals, such as Fe, Co, Ni, and Mo via powder consolidation techniques . As a result of the mixed ceramic–metallic bonding, cermets usually exhibit superb hardness (15–35 GPa), , remarkable wear/oxidation resistance, , and excellent chemical/thermal stability. ,, Despite this unique combination of physical properties, the Achilles’ heel of cermets is their lack of ductility and poor room-temperature toughness (e.g., 5–25 MPam 1/2 ). ,,, Therefore, people have made tremendous effort over the past years in the compositional and microstructural design of cermets in order to improve their toughness/ductility. ,, At the current moment, fabrication of cermets is mainly based on a variety of ex situ methods derived from powder metallurgy. While these fabrication methods have been widely adopted, fine-tuning of the fabrication parameters, such as sintering temperature and sintering cycling, is necessary to improve their toughness/ductility. Unfortunately, despite these prior efforts, cermets are still plagued by the lack of ductility, which may be attributed to the inherent brittleness of ceramics. , Therefore, to the best of our knowledge, no ductility in cermets has been ever reported yet.…”
mentioning
confidence: 99%
“…Thus, the optimal mechanical properties of cermet can be obtained in cermet C or D. Figure shows the crack propagation path of the cermet A and C. Crack deflection (as shown by circles) and crack bridging (as shown by squares) were discovered. More fracture energy consumption caused by crack deflection and crack bridging in changing the direction of crack propagation is advantageous to the improvement of toughness . So, the toughening mechanisms of TiN‐based cermets includes crack deflection and crack bridging.…”
Section: Resultsmentioning
confidence: 99%
“…However, interest in toughening Ti(C,N)‐based cermets has exploded recently . To date, researchers have shown that fibre‐reinforced composites, such as whiskers or tubes in the secondary phase, can be effectively enhanced to achieve better mechanical properties . Peng et al prepared Ti(C,N)‐based cermets containing 2.5 wt.% SiC whiskers by spark plasma sintering, which, compared to cermets without SiC whiskers, can increase the flexural strength and Vickers hardness by 66% and 5.8%, respectively.…”
Section: Introductionmentioning
confidence: 99%